58.5k views
5 votes
Tessa solves the equation below by first squaring both sides of the equation HELP PLEASE

Tessa solves the equation below by first squaring both sides of the equation HELP-example-1

2 Answers

6 votes

Answer:

-7

Explanation:

Khan academy

User Ian McMahon
by
5.0k points
2 votes

Answer:

-7

Explanation:


\sqrt{ {x}^(2) - 3x - 6} = x - 1

Squaring on both sides:


{x}^(2) - 3x - 6 = {(x - 1)}^(2)

Use the formula:
{(a - b)}^(2) = {a}^(2) - 2ab + {b}^(2)


{x}^(2) - 3x - 6 = {x}^(2) - 2x + 1

Combine like terms.


{x}^(2) - {x}^(2) - 3x + 2x = 1 + 6


- 3x + 2x = 7

Calculate


- x = 7


x = - 7

Hope this helps...

Good luck on your assignment..

User Berhir
by
4.7k points